-3 < y < 6
y < -3 or y > 6
y > -3 or y > 6
y < 3 or y < 6
Correct answer is A
y2 - 3y > 18 = 3y - 18 > 0
y2 - 6y + 3y - 18 > 0 = y(y - 6) + 3 (y - 6) > 0
= (y + 3) (y - 6) > 0
Case 1 (+, +) → (y + 3) > 0, (y - 6) > 0
= y > -3 y > 6
Case 2 (-, -) → (y + 3) < 0, (y - 6) < 0
= y < -3, y < 6
Combining solution in case 1 and Case 2
= x < -3y < 6
= -3 < y < 6
The height of a cylinder is equal to its radius. If the volume is 0.216 π m3. Calculate t...
If (K2)6 * 36 = 35(K4)5, what is the value of k?...
In the diagram, ∠ABC and ∠BCD are right angles, ∠BAD = t and &a...
Express 2x+3−1x−2 as a simple fraction...
Find the gradient of the line passing through the points (-2, 0) and (0, -4)...
Find the value of x satisfying x2 - 13 < 2x5 + \(\frac{1}{...
A ship sets sail from port A (86oN, 56oW) for port B (86oN, 64oW), which is clos...
Solve the inequality (x - 3)(x - 4) ≤ 0...
If the numbers M, N, Q are in the ratio 5:4:3, find the value of 2N−QM...